2005
DOI: 10.2989/16073610509486374
|View full text |Cite
|
Sign up to set email alerts
|

Development of speech sounds and syllable structure of words in Zulu-speaking children

Abstract: This study investigated development of speech sounds and syllable structure of words in 18 Zulu-speaking children between the ages of 3.0 and 6.2. A 100-word spontaneous conversational sample was elicited from each subject. All samples were transcribed phonetically by a stringent transcription procedure. The UNIBET was used to code the transcription into computer recognisablesymbols. The Phonetic Calculator Program (PCP) analysed the samples in terms of speech sound inventory, syllable structure of words and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Xhosa-speaking children made fewer errors at comparable ages to English-speaking children (and this difference was significant when comparing phonemes that exist in both languages), but the same phonemes (largely fricatives and liquids) were errorful for both groups. Naidoo (2003) also found that Zulu-speaking children aged 3 to 6 produced longer and more accurate strings of syllables than their English-speaking peers. Both Xhosa and Zulu have more long, multisyllabic words, but with simpler syllabic structure within the syllables (fewer clusters and fewer closed syllables, ending in a consonant) than English.…”
Section: General Acquisition Of Phonologymentioning
confidence: 89%
See 1 more Smart Citation
“…Xhosa-speaking children made fewer errors at comparable ages to English-speaking children (and this difference was significant when comparing phonemes that exist in both languages), but the same phonemes (largely fricatives and liquids) were errorful for both groups. Naidoo (2003) also found that Zulu-speaking children aged 3 to 6 produced longer and more accurate strings of syllables than their English-speaking peers. Both Xhosa and Zulu have more long, multisyllabic words, but with simpler syllabic structure within the syllables (fewer clusters and fewer closed syllables, ending in a consonant) than English.…”
Section: General Acquisition Of Phonologymentioning
confidence: 89%
“…Naidoo (2003) working on Zulu and Lewis and Roux (1996) working on Xhosa found that clicks were produced accurately later than other consonants. Lewis and Roux noted that children aged 1;6 to 5;5 acquiring Xhosa as their first language substituted clicks for other clicks, simplified clicks to become non-click consonants with the same place of articulation, or reduced clicks by removing an aspect of articulation such as nasalisation.…”
Section: Acquisition Of Clicksmentioning
confidence: 99%
“…Use has been made of rough translations from English (Suzman, 1991). But languages differ in terms of the size and content of speech sound inventory, the phonotatic constraints of the language, the syllable structures of words and the phonetic complexity of the sounds (Naidoo et al, 2005). The norms of one language can thus not necessarily be applied to other languages.…”
Section: Acquisition Studies In African Languagesmentioning
confidence: 99%
“…The norms of one language can thus not necessarily be applied to other languages. Language-specific normative data are critical in speech-language therapy, as they facilitate the differentiation between true speechlanguage pathology and speech-language difference (Naidoo et al, 2005). In addition to normative data assisting in identifying the presence or absence of a problem and making early and appropriate referrals possible, it facilitates the identification of goals and procedures for treatment, as these are usually based on developmental processes (Creaghead et al, 1989).…”
Section: Acquisition Studies In African Languagesmentioning
confidence: 99%
See 1 more Smart Citation